RISIKO ERGONOMI DAN KELUHAN MUSKULOSKELETAL PADA PEKERJA ADMINISTRASI: TINJAUAN LITERATUR - Uus Rusmawan; Agung Cahyono Triwibowo; Sandra Hakiem Afrizal (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
With technology and digital transformation, administrative tasks have been severely changed leading to extended periods of sitting with increased risk for musculoskeletal disorders (MSDs). This review presents a systematic inquiry of the ergonomic risks factors and musculoskeletal complaints in administrative staff, including articles published during 2020 to 2025. The review followed the PRISMA and accessed Scopus, PubMed, ScienceDirect, and Web of Science databases. Inclusion criteria 10 studies were included on the basis of inclusion criteria regarding ergonomic risk factors, work posture, and preventive interventions. It is evident that poor worker postures, prolonged static sitting, repetitive movements and lack of ergonomic knowledge are the major factors that lead to MSDs, most commonly involving the neck, shoulders and lower back. Psychosocial factors, such as high strain at work and bullying at the workplace can also increase musculoskeletal pain and delay recovery. The effectiveness of interventions, such as ergonomic training, workstation modifications, job rotation and introduction of assistive technologies like exoskeletons was found to be inconsistent emphasizing the necessity for well-structured ergonomics programs with workers’ involvement. In conclusion, holistic approaches (physical, psychological, organizational) should be considered in order to minimize ergonomic hazards and enhance health, productivity, and well-being of administrative staff.